Morphological Changes of Gingiva in Streptozotocin Diabetic Rats - C. Tesseromatis; A. Kotsiou; H. Parara; E. Vairaktaris; M. Tsamouri (International Journal of Dentistry)
Gingivitis and periodontitis are chronic bacterial diseases of the underlying and surrounding tooth tissues. Diabetes mellitus is responsible for tooth deprivation both by decay and periodontal disease. The streptozotocin-induced diabetes results in a diabetic status in experimental animals similar to that observed in diabetes patients. The aim of the study was to investigate the relationship between the gingival lesions and the microangiopathy changes in streptozotocin-induced diabetes mellitus. Forty male Wistar rats were divided into two groups (control and experimental). Diabetes mellitus was induced by 45 mg/kg IV streptozotocin. The histological investigation of the marginal gingival and the relevant gingival papilla showed inflammation of the lamina propria and the squamous epithelium as well as marked thickness of the arteriole in the diabetic group, but no changes were observed in the control group. The results suggested a probable application of a routine gingival histological investigation in diabetic patients in order to control the progress of disease complications. It may be concluded that histological gingival investigation can be used as a routine assay for the control of the diabetic disease and prevention of its complications.